2023
DOI: 10.1111/irv.13131
|View full text |Cite
|
Sign up to set email alerts
|

Viral co‐infection with human respiratory syncytial virus in suspected acute and severe respiratory tract infections during COVID‐19 pandemic in Yaoundé, Cameroon, 2020–2021

Abstract: Background Acute lower respiratory tract infections (ALRIs) are one one of the leading causes of morbidity and mortality among people of all ages worldwide, particularly in low‐ and middle‐income countries (LMICs). The purpose of this study was to determine epidemiological characteristics of respiratory viruses in acute respiratory infection (ARI) patients during the COVID‐19 pandemic in Yaoundé, Cameroon. Methods Patients were monitored for respiratory symptoms as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Many studies conducted during the COVID-19 pandemic reported possible coinfections of SARS-CoV-2 with other respiratory pathogens, including bacteria, fungi, and viruses [ 12 , 34 , 35 ]. In our three-year follow-up study, a rate of 7.2% of coinfections was detected, which is consistent with other reports [ 4 , 36 , 37 ]. Seven types of seasonal respiratory viruses were identified in mixed infections with SARS-CoV-2, among which RSV was the most common co-pathogen.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies conducted during the COVID-19 pandemic reported possible coinfections of SARS-CoV-2 with other respiratory pathogens, including bacteria, fungi, and viruses [ 12 , 34 , 35 ]. In our three-year follow-up study, a rate of 7.2% of coinfections was detected, which is consistent with other reports [ 4 , 36 , 37 ]. Seven types of seasonal respiratory viruses were identified in mixed infections with SARS-CoV-2, among which RSV was the most common co-pathogen.…”
Section: Discussionsupporting
confidence: 93%
“…This manuscript compares influenza data before and during the COVID-19 pandemic and describes SARS-CoV-2 data during the period of co-circulation of both respiratory viruses in Cameroon. (12.6% vs. 12.8%) during the pandemic period [11]. The reason for the higher SARS-CoV-2 detection rate in the latter study is due to the mixed target population, which consisted of persons captured by the influenza sentinel surveillance and from facilities testing suspected cases of COVID-19.…”
Section: Discussionmentioning
confidence: 69%
“…A recent study by Moumbeket et al. in Cameroon found almost equal circulation of influenza virus and SARS‐CoV‐2 (12.6% vs. 12.8%) during the pandemic period [11]. The reason for the higher SARS‐CoV‐2 detection rate in the latter study is due to the mixed target population, which consisted of persons captured by the influenza sentinel surveillance and from facilities testing suspected cases of COVID‐19.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, the presence of one virus does not exclude the possibility that a second infection is present simultaneously. 5 Epidemiology suggests, furthermore, that co-infection from different pathogens is frequent because of common risk factors such as crowded living spaces, lapses in hand hygiene, social interactions, insufficient distancing, and other health determinants. 6…”
Section: Introductionmentioning
confidence: 99%